Biochemical Profile by GC–MS of Fungal Biomass Produced from the Ascospores of Tirmania nivea as a Natural Renewable Resource - Jamal M. Khaled; Naiyf S. Alharbi; Ramzi A. Mothana; Shine Kadaikunnan; Ahmed S. Alobaidi (Journal of Fungi, 2021)
The edible fruiting bodies of desert truffles are seasonally collected and consumed in many regions of the world. Although they are very expensive, they are bought and sold as a result of considerable scientific reports confirming their health and nutritional benefits. This study aimed to conduct laboratory production of the fungal biomass of Tirmania nivea as a natural renewable resource of many active biological compounds using an artificial growth medium. The T. nivea collected from Hafar Al-Batin, which is north of Saudi Arabia, and their ascospores were harvested and used to produce fungal biomass in potato dextrose broth. The cultivation was conducted using a shaking incubator at 25 °C for two weeks at 200 rpm. The crud extracts of the fungal biomass and mycelium-free broth were prepared using ethyl acetate, methanol and hexane. Preliminary gas chromatography–mass spectrometry (GC–MS) analysis and their biological activity as antimicrobial agents were investigated. The results showed that the crude extracts have biological activity against mold, yeast and bacteria. The preliminary GC–MS analysis reported that the fungal biomass and extracellular metabolites in the growth medium are industrial renewable resources of several biological compounds that could be used as antifungal, antibacterial, antiviral, anticancer, antioxidant, anti-trypanosomal and anti-inflammatory agents.